Still Unwilling to Pay: An Empirical Analysis of 50 U.S. Newspapers' Digital Subscription Results. Issue 4 (20th April 2020) - Chyi, Hsiang Iris; Ng, Yee Man Margaret
Abstract: U.S. newspapers' digital experiment has been going on for more than two decades, with Christensen's disruptive technology thesis providing theoretical support for the industry's digital transformation process. Most newspapers expanded their digital offerings, erecting paywalls since 2011. However, little is known about local newspapers' paywall results. To extend media economics research on digital news consumption and to assess the influence and practicality of the disruption theory in the context of the newspaper business, this study systematically examines consumer demand for 50 major U.S. newspapers' multiplatform products through analyzing their circulation and pricing data. Results reveal that they charged digital subscribers a fraction of the print subscription price, but digital subscribership remained small, contributing only 3% of total reader revenue. Digital performance as weak as such raises concerns about the viability of digital subscriptions as a revenue source, provides support for the "online news as an inferior good" thesis, and calls for a reassessment of self-disruption as a practical strategy for newspaper firms.